The Issues of the Relationship of Grandparents and Grandchildren in the Light of Physical Activity - Herpainé Lakó, Judit (European Journal of Mental Health, 2014)
This study focuses on the role of certain factors responsible for physical and mental health, paying particular attention to the relationship between the family – particularly the grandparents – and physical education. Nowadays, the involvement of grandparents into the education of grandchildren is of high importance for the families. Our research shows that today, when parents’ work leads to a difficult and tough situation, the role of grandparents is very important in the life of the family. Our study clearly shows that the relationship of grandparents and grandchildren depends primarily on the quality of time spent together, i.e. on its content and emotional values.